Intellectual capital and sustainable growth of listed non-financial firms in Nigeria - Oyeyemi, Ogundajo Grace; Ayodele, Abiola Oluwatobi; Olawale, Osinowo Olalekan; David, Olunuga Olusoji; Chukwuekwu, Ojianwuna; Abimbola, Busari Tajudeen (International Journal of Business, Economics and Management, 2025)
Businesses that prioritize sustainability often gain a competitive edge in the marketplace. However, research suggests that non-financial firms in Nigeria are struggling to incorporate various elements of intellectual capital into their operations, threatening their corporate sustainability. While there is considerable literature on intellectual capital and sustainability in the financial sector, there is limited research on this topic in Nigeria's non-financial firms, which are vital to the economy. This study, therefore, investigates the impact of intellectual capital on the corporate sustainability of non-financial firms listed in Nigeria. The study employed an ex-post facto research design, focusing on 32 companies listed in the industrial and consumer goods sectors on the Nigerian Exchange as of December 31, 2020. Using a purposive sampling technique, a sample of 20 firms was selected for analysis over a 15-year period (2007–2021). The data were sourced from the published annual financial statements of the selected firms, with the reliability of the data ensured by statutory audits and certifications from regulatory agencies. Data analysis was conducted using both descriptive and inferential statistics, with a focus on the System Generalized Method of Moments (SGMM) at a 10% significance level. The findings indicate that intellectual capital significantly influences earnings sustainability (W(6, 287) = 95.26, p < 0.10). The study concludes that intellectual capital plays a crucial role in enhancing the corporate sustainability of non-financial firms in Nigeria. Consequently, it is recommended that these firms integrate intellectual capital into their operations to strengthen their sustainability efforts.